KOMUNIKASI ANTARPERSONAL DALAM PROSES REHABILITASI SOSIAL DI RUMAH SINGGAH DINAS SOSIAL KOTA BEKASI (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the role of interpersonal communication in the social rehabilitation process at the Bekasi City Social Service Shelter. Interpersonal communication plays a crucial role in building trust between staff members, including part-time government employees (P3K) and daily contract workers (PHL), and beneficiaries known as People with Social Welfare Problems (PPKS), such as street children, homeless individuals, beggars, and other vulnerable groups. This research uses a qualitative approach with a case study method, employing in-depth interviews, participatory observation, and documentation as data collection techniques. The findings indicate that the effectiveness of social rehabilitation is strongly influenced by the quality of interpersonal communication, which includes openness, empathy, supportiveness, positive attitudes, and equality. The shelter employs 18 staff members, consisting of 13 part-time P3K workers and 5 daily contract workers. The Social Service has implemented various development programs, including mental, physical, and spiritual guidance, delivered by qualified professionals. Although the service duration is set at a maximum of seven days, in practice it often exceeds this limit due to challenges in tracing personal data and identifying beneficiaries. During this process, the Social Service conducts referrals and collaborates with various institutions, including other regional governments and the Ministry of Social Affairs. The main obstacles include limited budget, suboptimal coordination, limited human resources, and communication difficulties with certain beneficiaries. Efforts to address these challenges include maximizing service delivery, strengthening collaboration, and expanding networks with relevant institutions. In conclusion, effective interpersonal communication significantly enhances the success of social rehabilitation and promotes behavioral change and independence among beneficiaries.